2018
DOI: 10.1590/abd1806-4841.20186477
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of the Simplified Psoriasis Index (SPI) into Brazilian Portuguese

Abstract: BackgroundThe Simplified Psoriasis Index is a tool that assesses the current severity, psychosocial impact, past history and interventions in patients with psoriasis through separate components. Two versions are available, one in which the current severity of the disease is evaluated by the patient themselves and another by the physician.ObjectivesTranslate the Simplified Psoriasis Index into Brazilian Portuguese and verify its validity.MethodsThe study was conducted in two stages; the first stage was the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…8,10 There are now validated translations of SPI into at least 7 languages with published reports of its successful use in Dutch, French, and Portuguese translation. [22][23][24] The present study has demonstrated the validity and reliability of SPI in translation and its suitability for use in Thai patients with psoriasis.…”
Section: Discussionmentioning
confidence: 83%
“…8,10 There are now validated translations of SPI into at least 7 languages with published reports of its successful use in Dutch, French, and Portuguese translation. [22][23][24] The present study has demonstrated the validity and reliability of SPI in translation and its suitability for use in Thai patients with psoriasis.…”
Section: Discussionmentioning
confidence: 83%